The burden of Galileo's controversy: The Jesuit revisiting of the Aristotelian cosmos in Collegio Romano (1618-1677) - Carolino, L. M. (Galilaeana, 2023)
When studying the controversy prevailing between Galileo and the Jesuits over the comets of 1618, historians tend to focus primarily on the works that led to the publication of Il Saggia- tore in 1623. This article demonstrates that the echoes of this controversy reverberated inside the walls of the Collegio Romano well beyond the publication of Galileo’s chef-d’oeuvre. Its philosophy and mathematics professors strove to maintain – in opposition to Galileo – the Aristotelian principle that the heavens were ontologically superior to the terrestrial region throughout decades. Even after adhering to the planetary system of Tycho Brahe and the con- cept of celestial fluidity, they persisted in arguing that no corruption ever took place in the celestial region. Hence, accepting Tycho’s astronomical theories meant the seventeenth-cen- tury Collegio Romano professors had to reject the Ptolemaic astronomical framework even if not necessarily denying the very core of the Aristotelian cosmology. Thus, Collegio Romano remained the champion of philosophical orthodoxy within the Jesuit educational network.